2008
DOI: 10.1007/s12015-008-9018-0
|View full text |Cite
|
Sign up to set email alerts
|

Very Small Embryonic-Like (VSEL) Stem Cells: Purification from Adult Organs, Characterization, and Biological Significance

Abstract: In this review, we discuss current views of the bone marrow (BM) stem cell (SC) compartment and present data showing that BM contains heterogeneous populations of hematopoietic (H)SCs and non-HSCs. These cells are variously described in the literature as: endothelial progenitor cells (EPCs); mesenchymal (M)SCs; multipotent adult progenitor cells (MAPCs); marrow-isolated adult multilineage inducible (MIAMI) cells; and multipotent adult (MA)SCs. In some cases, it is likely that similar or overlapping populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 56 publications
1
56
0
1
Order By: Relevance
“…Experimental studies in murine models of acute myocardial infarction (AMI) demonstrated that this rare population of cells is also enriched in early markers of cardiac and endothelial lineages (GATA-4, Nkx2.5/Csx, VE-cadherin, von Willebrand factor). VSELs migrated to stromal-derived factor-1 (SDF-1) gradient and underwent rapid mobilization into peripheral blood in experimental AMI mouse models (4,5). In addition to BM, VSELs were also identified in several murine solid organs including the heart and brain, as well as in umbilical cord blood and peripheral blood in adult humans (3,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies in murine models of acute myocardial infarction (AMI) demonstrated that this rare population of cells is also enriched in early markers of cardiac and endothelial lineages (GATA-4, Nkx2.5/Csx, VE-cadherin, von Willebrand factor). VSELs migrated to stromal-derived factor-1 (SDF-1) gradient and underwent rapid mobilization into peripheral blood in experimental AMI mouse models (4,5). In addition to BM, VSELs were also identified in several murine solid organs including the heart and brain, as well as in umbilical cord blood and peripheral blood in adult humans (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…VSELs migrated to stromal-derived factor-1 (SDF-1) gradient and underwent rapid mobilization into peripheral blood in experimental AMI mouse models (4,5). In addition to BM, VSELs were also identified in several murine solid organs including the heart and brain, as well as in umbilical cord blood and peripheral blood in adult humans (3,5). We envision that VSELs are quiescent progeny of epiblast-derived PSCs that are deposited during organogenesis in developing organs (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…They also express other germ line markers like Mouse vasa homologue (MVH), STELLA, NOBAX, FRAGALLIS, Dead end protein homolog 1 (DND1), Histone deacetylase 6 (HDAC6) [68]. VSELs have a high telomerase activity [69] and do not express MHC I [70]. They also share similar surface antigens including CXCR4 [71] with CSCs.…”
Section: Very Small Embryonic/epiblast-like Stem Cellsmentioning
confidence: 99%
“…60,61 The presence of these developmentally primitive stem cells in adult tissues can be explained by the possibility that early during embryogenesis not all of the stem cells differentiate into monopotent tissue-committed stem cells, but some survive in developing organs as a dormant backup population of primitive stem cells.…”
Section: 74mentioning
confidence: 99%